Expectations of reward and efficacy guide cognitive control allocation - R. Frömer (Nature Portfolio, 2021)
People only exert cognitive effort if they think the benefits outweigh the costs. Here, the authors show that people assess these benefits by considering expected rewards and how much their effort matters for obtaining those rewards, and then integrating these to determine how much effort to exert.